Vertigo Induced During Coitus - Lee, Sun-Uk; Kim, Hyo-Jung; Koo, Ja-Won; Choi, Jeong-Yoon; Kim, Ji-Soo (Frontiers in Neurology, 2019)
Objectives: The aim of this study was to describe the clinical features of vertigo developed during the sexual intercourse. Methods: We retrospectively reviewed the clinical and laboratory findings of seven patients who reported recurrent vertigo during the sexual intercourse. Results: All the patients reported spinning sensation for a few minutes to one hour, which developed during the coitus. Most patients (6/7, 86%) reported associated auditory symptoms including tinnitus (n=4), ear fullness (n=2), autophony (n=1), hearing impairment (n=1) or hyperacusis (n=1). Four patients reported the vertigo to occur exclusively during sexual intercourse or masturbation while the other three patients also experienced vertigo during other physical activities. Underlying disorders included Meniere’s disease (n=3), superior canal dehiscence (n=1), and high jugular bulb anomaly (n=1) while the remaining two patients had no identifiable causes. Conclusions: Various disorders may cause coital vertigo probably due to disruption of the mechanism that normally refrains the increased intracranial pressure from being directly transferred to the peripheral vestibular organs.